2012
DOI: 10.3109/08941939.2011.636476
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hepatic Arterial Reconstruction on Orthotopic Liver Transplantation in the Rat

Abstract: Orthotopic liver transplantation (OLT) models in rats have been investigated in many studies, but detailed information on the impact of hepatic artery (HA) reconstruction on postoperative factors remains to be investigated. HA reconstruction also requires advanced skills. The effect of the reconstruction of the HA by a hand-suture technique in rats with a whole-liver syngeneic graft was investigated. Long-term survival, histopathological assessment, immunohistological evaluation, and blood biochemistry were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Drug-induced DNA damage is not identified by the TUNEL assay unless it is coupled to the apoptotic response (34). In addition, this technique can detect early-stage apoptosis in systems where chromatin condensation has begun and strand breaks are fewer, even before the nucleus undergoes major morphological changes (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced DNA damage is not identified by the TUNEL assay unless it is coupled to the apoptotic response (34). In addition, this technique can detect early-stage apoptosis in systems where chromatin condensation has begun and strand breaks are fewer, even before the nucleus undergoes major morphological changes (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Orthotopic liver transplantation was performed using the “two-cuff technique” as previously described [11, 18]. Briefly, the donors and recipients were anesthetized with the ether.…”
Section: Methodsmentioning
confidence: 99%
“…It has been amply demonstrated that - in contrast to the human situation - OLT and P-OLT in rats can be successfully performed without the technically complicated rearterialization of the graft [3,9,15,94]; nonetheless, the arterial flow has essential functions, and omitting rearterialization can substantially influence bile duct circulation (and thereby the rate of biliary complications) [18,95,96], graft microcirculation [97], and immunological functions [98]. This was also confirmed during our own investigations: we observed considerable differences in hepatocellular injury (AST and ALT levels) and graft microcirculation with and without arterial reconstruction [unpubl.…”
Section: Technical Issues Concerning P-olt In Ratsmentioning
confidence: 99%